Implementasi Manajemen Kepala Sekolah Untuk Meningkatkan Sarana dan Prasarana SMP Unggul Calang - Husnul Hamdi; M. Anas Maarif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research analyzes the implementation of principal management in improving means and infrastructure in Junior High School Calang, Aceh Jaya Regency. The management of means and infrastructure is a crucial element in supporting the learning process, yet the school still faces significant constraints as it is still in the development stage. This qualitative research with a case study design was implemented on March 25–April 25, 2024, with the subject principal, the deputy principal of the area of infrastructure means, and the school operator. Data were collected through observation, in-depth interviews, and documentation, then analyzed descriptively through data reduction, data presentation, and inference drawing. Data validity was obtained through credibility triangulation. The results of the study indicated that principals played the roles of managers (planners and managers of resources), movers (motivators), administrators (managers of APBS archives and reports), and leaders (in charge of reporting). Applied strategies include immovable property planning, procurement through purchase, grant, rehabilitation and cooperation, arrangement through inventory, storage and maintenance, as well as direct and indirect use. Supporting factors included principal commitment and school committee support, while hindering factors were budget constraints and coordination between units.